2013
DOI: 10.1590/s1677-32252013000200011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dialysis duration and parathyroid hormone on the clinical and radiographic oral conditions of pre-transplant patients with chronic kidney disease

Abstract: Aim: To evaluate the oral conditions of patients with chronic kidney disease undergoing dialysis and to determine the influence of dialysis duration and bone metabolism on the prevalence and severity of the alterations found. Methods: The simplified oral hygiene index (OHI-S), prevalence of dental caries (decayed, missing filled teeth index, DMFT), and the periodontal screening and recording (PSR) index were evaluated in 154 patients. Parathyroid hormone (PTH), calcium, phosphorus and urea measurements, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
1
6
1
2
Order By: Relevance
“…Queiroz et al evaluated the oral condition of patients with CKD undergoing dialysis and determined the influence of dialysis duration and bone metabolism on the prevalence and severity of the alterations. No significant correlation was observed between dialysis duration, biochemical alteration and oral health (33). These findings are compatible with our results, although we focused on bony changes of mandible.…”
Section: Discussionsupporting
confidence: 91%
“…Queiroz et al evaluated the oral condition of patients with CKD undergoing dialysis and determined the influence of dialysis duration and bone metabolism on the prevalence and severity of the alterations. No significant correlation was observed between dialysis duration, biochemical alteration and oral health (33). These findings are compatible with our results, although we focused on bony changes of mandible.…”
Section: Discussionsupporting
confidence: 91%
“…[ 16 ] The brown tumor development was seen only in one patient in the study, which was conducted by Queiroz et al . [ 28 ] on 174 hemodialysis patients. Vidyullatha et al .…”
Section: Discussionmentioning
confidence: 99%
“…Queiroz et al (2013) 40 found urea reduction ratio of <65%, in patients with higher frequencies of calculus in pre-transplant patients with chronic kidney disease.…”
Section: Icmentioning
confidence: 98%